Tingkat Pendidikan, Literasi Keuangan, dan Perencanaan Keuangan terhadap Perilaku Keuangan UMKM di Surakarta - Ari Susanti; . Ismunawan; . Pardi; Elia Ardyan (Sekolah Tinggi Ilmu Manajemen YKPN Yogyakarta, 2018)
Abstract This study aims to determine the level of education, financial literacy, and financial planning in Small and Medium Enterprises in Surakarta and its influence on financial behavior. The sample of research is 115 MSMEs residing in Surakarta. Data analysis using multiple linear analysis. The results showed that the level of education, financial literacy, and financial planning have a positive and significant impact on the financial behavior of MSMEs. Its managerial implications are needed to foster a healthy understanding of financial behavior in MSMEs by attending various training on finance and management of small and medium enterprises.